Basic Theory of Islamic Education Management - Danusiri Danusiri (FITK UIN Walisongo, 2019)
The purpose of this research is to find the principles science about the management of Islamic education. The realization of this principles are collection of various concepts, propositions, and theoretical theory (basic theory) on tahlili interpretation of a number of verses of the Qur'an or the syarah hadith tahlili to find the compound between the interpretation of verses or syarah hadiths with nomenclatures in concept, proposition, and theory of science of management of Islamic education. The result found 13 main principles of content and basic theory of Islamic education management namely : first, Islamic Education Planning is long-term planning until hereafter; Second, Manager responsibility that each action is asked accountability ; ThirdThe organizing principle is every functionary in an institution must be loyal to the top leader in the implementation of the task, etc.Abstrak Tujuan dari penelitian ini adalah untuk menemukan prinsip sains tentang manajemen pendidikan Islam. Realisasi prinsip-prinsip ini adalah kumpulan berbagai konsep, dalil, dan teori teoritis (teori dasar) tentang tafsir tahlili sejumlah ayat Al-Qur'an atau hadits syarah tahlili untuk menemukan senyawa antara tafsir ayat atau hadis syarah. dengan nomenklatur dalam konsep, proposisi, dan teori sains manajemen pendidikan Islam. Hasilnya menemukan 13 prinsip utama isi dan teori dasar manajemen pendidikan Islam yaitu: pertama, Perencanaan Pendidikan Islam adalah perencanaan jangka panjang sampai akhirat; Kedua, tanggung jawab Manajer bahwa setiap tindakan diminta pertanggungjawaban; Ketiga. Prinsip pengorganisasian adalah setiap pejabat dalam suatu institusi harus loyal kepada pemimpin puncak dalam pelaksanaan tugas, dll.